Pengembangan Media Permainan Ajian Jaran Goyang Untuk Meningkatkan Efikasi Diri Siswa SMP - Ayuningtyas, Putri; Nawantara, Rosalia Dewi; Setyaputri, Nora Yuniar (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2022)
The current field phenomenon says that some junior high school-age children in the Grogol Kediri area are less able to choose something suitable for themselves because they do not understand the importance of self-efficacy. Therefore, the role of the guidance and counseling teacher is very important in today's conditions to provide service through the media. The media can use the favorite traditional arts of Kediri teenagers, namely Jaranan art. This media can be called the game media "Ajian Jaran Goyang" with tools including jaran kepang, track boards, movement cards, udeng, development questions, and guidebooks. This study uses the Borg & Gall R&D model and to produce media that can be accepted theoretically and practically. The research is currently entering its fourth stage, namely the expert test with a score of 72, the media development expert test with a score of 72, and the user trial with a score of 69.5. Based on these results, it can be concluded that the media game "Ajian Jaran Goyang" can be accepted theoretically with a very appropriate category to use to improve the self-efficacy of junior high school students through the noble meaning of the art of jaranan.